A study on design & development of betamethasone acetate and betamethasone sodium phosphate extended-release suspension - Bansal, Amit; Sardana, Satish; Wadhwa, Tarun (Creative Pharma Assent, 2025)
Background: The development of an injectable composition of betamethasone sodium phosphate and betamethasone acetate with an equivalent drug release profile to the marketed reference drug product,